[3, 3]‐Sigmatropic Rearrangement/Allylboration/Cyclization Sequence: Enantioenriched Seven‐Membered‐Ring Carbamates and Ring Contraction to Pyrrolidines. Issue 3 (4th December 2015) - Macé, Aurélie; Touchet, Sabrina; Andres, Patricia; Cossío, Fernando; Dorcet, Vincent; Carreaux, François; Carboni, Bertrand
Abstract: The combination of in situ generated α‐isocyanato allylboronic esters and aldehydes afforded seven‐membered‐ring enecarbamates with high levels of diastereo‐ and enantiocontrol. They were easily converted into diversely substituted 1, 3‐oxazepan‐2‐ones. An unprecedented rearrangement of 5‐acetoxy‐7‐aryl or styryl derivatives led to tetrasubstituted pyrrolidines. A computational study provides evidence on the feasibility of the proposed mechanism of this unusual ring contraction. Abstract : Honey I shrunk the rings : A new protocol for the diastereo‐ and enantiocontrolled synthesis of seven‐membered‐ring ene carbamates is described. These compounds were easily converted into diversely substituted 1, 3‐oxazepan‐2‐ones. Tetrasubstituted pyrrolidines were obtained by an unprecedented ring contraction rearrangement of a 5‐acetoxy derivative in the presence of trifluoroboron etherate.